2018
DOI: 10.1080/13543776.2018.1495708
|View full text |Cite
|
Sign up to set email alerts
|

HIV cure: global overview of bNAbs’ patents and related scientific publications

Abstract: This article provides a global overview of patent deposits for broadly neutralizing antibodies (bNAbs), which have emerged as a key strategy for HIV cure and future HIV vaccines. Scientific and technological barriers to the discovery of an effective HIV vaccine in the last 40 years have raised concerns on the potential for relevant advances in this area. Nevertheless, recent breakthrough studies have identified novel immune pathways for new innovative HIV vaccine and HIV cure strategies. Areas covered: In our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Secondly, the "deep latency" strategy adopt the opposite approach; proviral HIV is silenced so that it cannot rebound (Elsheikh et al, 2019). Lastly, recent studies have isolated several neutralizing monoclonal antibodies from HIV-infected patientsopening up the use of broadly neutralizing antibodies (bnAbs) as a potentially curative treatment for HIV (Possas et al, 2018). It has been suggested that bnAbs can control HIV replication and reactivate latent cells, although the use of these antibodies to specifically target HIV-1 in humans constitutes a major challenge (Shen et al, 2019).…”
Section: Therapeutic Strategies Based On Metabolic Pathwaysmentioning
confidence: 99%
“…Secondly, the "deep latency" strategy adopt the opposite approach; proviral HIV is silenced so that it cannot rebound (Elsheikh et al, 2019). Lastly, recent studies have isolated several neutralizing monoclonal antibodies from HIV-infected patientsopening up the use of broadly neutralizing antibodies (bnAbs) as a potentially curative treatment for HIV (Possas et al, 2018). It has been suggested that bnAbs can control HIV replication and reactivate latent cells, although the use of these antibodies to specifically target HIV-1 in humans constitutes a major challenge (Shen et al, 2019).…”
Section: Therapeutic Strategies Based On Metabolic Pathwaysmentioning
confidence: 99%
“…Humoral immune responses are critical for preventing, controlling, and eradicating HIV infection, as demonstrated by the numerous studies employing bNAbs [ 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 ]. The results of the Thai Phase III HIV Type 1 Vaccine Trial (RV144) demonstrated that antibody responses were responsible for the modest protection conferred by the administration of the ALVAC-HIV (vCP1521) prime and AIDSVAX B/E vaccine [ 8 ], further fueling the research on antibody responses in HIV infection and leading to the discovery of bNAbs and the design of new strategies for HIV prevention and eradication [ 254 , 255 ].…”
Section: Experimental Dissection Of Immune Responses In Siv Infectionmentioning
confidence: 99%